SUSTAINABLE SUGARCANE INITIATIVE : BETTER OPTION FOR CANE PRODUCTION - BISHNUPRIYA PATRA,; S.N. JENA,; STUTI DEBAPRIYA BEHERA,; PRIYANKA SAHOO, (The Bioscan, 2019)
A new methodology has been developed for better cane production in order to maintain the productivity level and to stabilize India’s rank in production on global market. This new technique is name as SSI. Under limited water supply, growth and productivity of some long duration crops like sugarcane was adversely affected. This chipping and chip planting method can curtail seed cost by 20000 to 25000 per ha that is direct benefit to the farmers. SSI improves the productivity of cane, efficiency of water use, land and labour. At same time it reduces the overall pressure on water resources, resulted in about 20 % higher yields. So, SSI is a better alternative to conventional sugarcane cultivation.